The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/1331677x.2014.974337
|View full text |Cite
|
Sign up to set email alerts
|

Scientometric approach of productivity in scholarly economics and business

Abstract: Some scientometric studies attempt to explain the factors affecting a country's scientific output, which is usually measured by proxy variables such as the number of articles and citations in internationally-renowned journals. This paper highlights the main drivers for scientific output in economics and business, namely, financing of education and research, population size, the number of scholarly journals and English as the official language. We use multiple OLS regressions and data provided by Web of Knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The sharing economy is not very different from other academic fields in geographical terms. Our data confirm the predominance the United States and some Asian countries, just as do studies on different research fields that highlight North America and Asia (in the last decades) as the most popular regions to retrieve information (Chatha et al, 2018;Dragos et al, 2014). This result is also similar to that of Arcidiacono et al (2018) who found an increasing evolution in the number of papers on sharing economy, mainly in an Anglo-American context.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The sharing economy is not very different from other academic fields in geographical terms. Our data confirm the predominance the United States and some Asian countries, just as do studies on different research fields that highlight North America and Asia (in the last decades) as the most popular regions to retrieve information (Chatha et al, 2018;Dragos et al, 2014). This result is also similar to that of Arcidiacono et al (2018) who found an increasing evolution in the number of papers on sharing economy, mainly in an Anglo-American context.…”
Section: Discussionsupporting
confidence: 87%
“…Systematic reviews frequently include a geographic analysis which includes data such as the location of the journals publishing on a specific topic, the region where the data were collected, or an author's country of affiliation (Niñerola et al, 2019). Although the findings vary depending on the topic under research, it is quite frequent that most of the papers considered were written in Anglophone countries, and especially in North America, although the last few decades have seen an increasing number of research studies originating in Asia (Chatha, Butt, Jajja, & Arshad, 2018;Dragos, Dinu, Pop, & Dabija, 2014).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…In addition, it has also been claimed that the emphasis on social components in the general mainstream of enterprise innovation activity is one of the strongest reasons for its successful functioning and development [11,12]. There is a considerable debate on measuring the efficiency of monetary resource allocation on research and development (RD) [13][14][15]. Table 1 offers an overview of the most important articles on this topic, showing the historic development of the analysis of this problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data on academic publications have been collected with the help of the Web of Science™ (hereinafter: WoS) system of the Institute for Scientific Information (ISI, now part of Thomson Reuters). There are some arguments for using its most important competitor, Scopus, of Reed Elsevier [15,65,66]; however, based on the number of papers and citations, largely independent of the field of science, an extremely high correlation between the "performance" of these two databases has been proven. The rigorous, systematic analysis of academic publications began only a few decades ago [67], but the publication and patent data can offer a longer time series.…”
Section: Databasesmentioning
confidence: 99%
See 1 more Smart Citation